GAMBARAN PENGETAHUAN DAN SIKAP IBU TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA ANAK PRASEKOLAH DI DESA GP.MUTIA KECAMATAN LANGSA KOTA - HENNIWATI . (Poltekkes Kemenkes Surabaya, 2017)
Objective:The objective of this reaserch is to know the description of mother's knowledge and attitude toward Clean and Healthy Life Behavior (CHLB) on preschool children in Mutia village, Langsa sub-district city in 2013.Method:The method used in this research is descriptive research method with cross sectional design. This method is used to reveal the description of mother’s knowledge and attitude towards Clean and Healthy Life Behavior (CHLB) on preschool children in Gp. Mutia Village, Langsa Kota sub-district. The study was conducted on May 16th to 25th, 2015 in Mutia village, Langsa Kota sub-district, Aceh.Result:The result of the research showed that 36 out of 45 respondents (80%) did not conduct clean and healthy life behavior, and only 9 out of 45 respondents (20%) had performed a clean and healthy life behavior. In addition, the result of this study also indicated that 30 out of 45 respondents (66%) did not have sufficient knowledge about clean and healthy life behavior, and only 15 out of 45 respondents (34%) had sufficient knowledge about clean and healthy life behavior. The results of this study also showed that 35 out of 45 respondents (78%) had a negative attitude.Conclusion:Based on the result of the study, the researcher concludes that there is influence between mother's knowledge and attitude toward Clean and Healthy Life Behavior (CHLB) on preschool children in Mutia village, Langsa Kota Sub-district, year 2015.Keywords: Knowledge, Attitude, CHLB.